2018
DOI: 10.5935/abc.20180275
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Performance of Isolated Left vs. Right Ventricular Pacing in Patients with Bradyarrhythmias: A Randomized Controlled Trial

Abstract: Background Considering the potential deleterious effects of right ventricular (RV) pacing, the hypothesis of this study is that isolated left ventricular (LV) pacing through the coronary sinus is safe and may provide better clinical and echocardiographic benefits to patients with bradyarrhythmias and normal ventricular function requiring heart rate correction alone. Objective To assess the safety, efficacy, and effects of LV pacing using an active-fixation coronary sinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(22 reference statements)
0
5
0
1
Order By: Relevance
“…After the exclusion of duplicates and non-relevant studies, 36 studies were retrieved for further full-text evaluation by reviewing study titles and abstracts. We further excluded three studies that were projected in cross-over manner [ 4 , 5 , 6 ], six trials that did not evaluate LVEF in the follow-up [ 7 , 8 , 9 , 10 , 11 , 12 ], seven studies in which information about RVAP was absent or RVAP was <20% [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], three studies in which patients were treated according to the ‘’ablate and pace” method [ 20 , 21 , 22 ], one trial with a short-term follow-up [ 23 ], one trial which was a prolonged follow-up of the so far included study, and one study because of statistical issues [ 24 ]. Finally, fourteen randomized controlled studies published in the period of 2008–2017 were included in this systematic review and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the exclusion of duplicates and non-relevant studies, 36 studies were retrieved for further full-text evaluation by reviewing study titles and abstracts. We further excluded three studies that were projected in cross-over manner [ 4 , 5 , 6 ], six trials that did not evaluate LVEF in the follow-up [ 7 , 8 , 9 , 10 , 11 , 12 ], seven studies in which information about RVAP was absent or RVAP was <20% [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], three studies in which patients were treated according to the ‘’ablate and pace” method [ 20 , 21 , 22 ], one trial with a short-term follow-up [ 23 ], one trial which was a prolonged follow-up of the so far included study, and one study because of statistical issues [ 24 ]. Finally, fourteen randomized controlled studies published in the period of 2008–2017 were included in this systematic review and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A similar result was reported by Crevelari; in her research, no hospitalization due to heart failure was observed. However, 23.5% of patients with RVP had over 10% LVEF reduction at the end of the follow-up [ 7 ]. According to the three meta-analyses, right ventricular non-apical electrode location ensures less harmful influence on LVEF in comparison with its apical location [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2019) предлагают для пациентов с брадиаритмиями и нормальной функцией желудочков, нуждающейся только в коррекции частоты сердечных сокращений, проводить изолированную ЭКС ЛЖ через коронарный синус, которая обеспечивает лучшие клинические и ЭхоКГ результаты. Проведение тканевого допплерографического анализа показало, что межжелудочковая диссинхрония в группе пациентов со стимуляцией ЛЖ наблюдалась реже на 22,4%, по сравнению с таковой у пациентов со стимуляцией ПЖ [11].…”
Section: Discussionunclassified
“…Despite the great benefit of the AV synchronized pacing, the endocardial lead at the apex of the right ventricle remained causing unwanted pacing 4 with wide QRS and complete left bundle branch block effect, with significant dyssynchrony of the left ventricular walls given rise to a second problem: the "Ventricular Pacemaker Syndrome or Wide QRS Syndrome", 7 whose prevention and treatment gave origin to resynchronization therapy. [5][6][7][8] . Despite being present in the entire cardiac stimulation, this dyssynchrony was neglected for a long time due to the great benefit resulting of the bradycardia correction.…”
Section: A Hidden and Deleterious Side Effectmentioning
confidence: 99%